ENVIRONMENTAL ADAPTATION: THE ARCHITECTURE OF RUMAH KAPITAN AND MUSI RIVERSIDE - Alfred Alfred; Uras Siahaan; Rumiati R. Tobing (International Journal on Livable Space, 2017)
Palembang’s Chinese community began inhabiting Kampung Kapitan 7 Ulu following the issuance of a mandate by Sultan Abdurrahman, granting the Chinese the privilege to inhabit the dry lands by the Musi River. Following the migration to the dry lands, the Chinese community implemented different forms of adaptation to the natural and socio-cultural environment to survive on the Musi Riverside, including in the form of residential architectures. This research is a case study, aiming to explore, examine and discuss the process of environmental adaptation and the different aspects that affect the residential architectures on the Musi Riverside. Analysis is done on the architecture of Rumah Kapitan, studying from the morphological and typological point of view, consisting of its positioning and orientation against the Musi River, spatial order, architectural form, and tectonics system, all of which are the manifestation of adaptation to the natural and socio-cultural environment of the Musi Riverside.  Keywords: adaptation; Musi riverside environment; Rumah Kapitan.